The misery of international law confrontations with injustice in the global economy - Linarelli, John (Oxford University Press, 2018)
This book challenges conventional justifications of economic globalization and eschews false choices. It is not about whether one is "for" or "against" international trade, foreign investment, or global finance. The issue is to resolve how, if we are to engage in trade, investment, and finance, we do so in a manner that is accountable to persons whose lives are affected by international law. The deployment of human rights for their part must be considered against the ubiquity of neoliberal globalization under law, and not merely as a discrete, benevolent response to it.